Development of Prelicensure Nursing Competencies in Caring for People With Disabilities Through Delphi Methodology. Issue 3 (May 2020) - Kronk, Rebecca; Colbert, Alison M.; Smeltzer, Suzanne C.; Blunt, Elizabeth
Abstract : Background: People with disabilities (PWDs) experience significant health disparities. The complex experience of disability requires that nurses are adequately and deliberately prepared to care for PWDs. However, there are no recognized nursing competencies to direct education and care. Purpose: The purpose of this study was to develop a set of nursing competencies to better prepare prelincensure nursing students to provide competent care to PWDs. Methods: A 2-round Delphi survey was administered to experts in the field of disabilities (n = 47, n = 35). Quantitative and qualitative methods were used to analyze data. Results: Three major themes emerged: unique knowledge, volume and repetition, and distinct disability culture. Competencies were reduced with a focus on 4 dimensions: environment and care, communication, culture, and referral. Conclusions: The 12 new competencies can serve as the foundation for the inclusion of disability content in nursing curricula. Abstract : Supplemental digital content is available in the text.